Nested Case-Control Study of Intervention in Early Infancy to Prevent Tuberous Sclerosis Complex–Associated Renal Angiomyolipoma - Shuo Dun; Lin Wan; Yang-Yang Wang; Qian Lu; Qi Zhang; Qiu-Hong Wang; Jia Wang; Hai-Qing Zhao; Li-Ping Zou (Kidney International Reports)
Introduction: In current studies, treatment of tuberous sclerosis complex (TSC)–related renal angiomyolipoma (RAML) was initiated only after clinical progression or the onset of symptoms, rather than at an earlier stage in the disease process. However, the previous case report indicated that early mammalian target of rapamycin (mTOR) inhibition in patients with TSC might prevent the development of TSC lesions. We performed this nested case-control study to evaluate whether prophylactic sirolimus initiation in early infancy prevented TSC-related RAML (TSC-RAML). Methods: A nested case-control study design was used, based on the Efficacy and Safety of Sirolimus in Pediatric Patients With Tuberous Sclerosis (ESOSIPT) study cohort. Children with TSC initiating sirolimus at age ≤ 3 months and without RAML at baseline comprised the case group (treatment group). Propensity score matching (1:3) was used to select the control group from the first visit patients who were aged > 3 months without mTOR inhibitor exposure. The incidence of RAML was compared via Kaplan-Meier method with log-rank testing. Results: Twenty-seven eligible children entered the study as a case group, and 81 patients who had not used mTOR inhibitors were matched. The log-rank test showed that the incidence of RAML between the 2 groups was statistically significant (P = 0.047). Short-term adverse events (AEs) were reported in 55.6% (15/27) of early-treated infants, predominantly grade 1 or 2 according to the common terminology criteria for AEs. Conclusion: The use of sirolimus in early infancy might have had potential benefits in preventing TSC-RAML, and the short-term AEs were usually mild or moderate.